Generation of any PDF from a Set of Equally likely Random Variables (Global Journal of Computer Science and Technology, 2014)
Computer quantization is important to consider in digital signal processing because it limits the accuracy of signals to be processed. In this paper we will talk about the quantization effect on system performance and use the result to make an improvement in the signal and systems field. Computers communicate with ones and zeros back and forth. The ones and zeros make a word that a computer send to another. Each character of the word is a bit and the word has eight bits. The word can be called a byte. One byte can have 256 different words. In general if we have eight bits register in a computer the dynamic rang of numbers are quantized to 256 levels. This may result in error because the number we want to process may not fall exactly in its level. The accuracy depend on the computer and the number of bits on a register. In this paper we want to use A/D quantization error .